Do environmental attitudes affect public acceptance of key enabling technologies? Assessing the influence of environmental awareness and trust on public perceptions about nanotechnology. (10th February 2023) - Todaro, Niccolò Maria; Gusmerotti, Natalia Marzia; Daddi, Tiberio; Frey, Marco
Abstract: Key Enabling Technologies (KETs) play a crucial role in modern societies due to their substantial contribution to cleaner production, sustainable development, and societal well-being across industrial sectors. However, to prompt the successful deployment of such technologies in diverse societal and market contexts, public acceptance constitutes a crucial requirement. As public knowledge of KETs is often limited, "cognitive shortcuts" – such as attitudes and personal beliefs – play a crucial role in shaping public opinion about enabling technologies. Drawing on the case of nanotechnology, the paper advances that environmental attitudes contribute to shape layman's perceptions about novel enabling technologies. Based on data collected from a survey of Italian citizens, the study investigates the influence of environmental awareness on public perceptions of benefits and risks of nanotechnology. By means of hierarchical regression equations, the study also tests the moderation of public trust in the environmental commitment of societal actors deemed responsible for nanotechnology development – i.e. high-tech companies, governmental agencies and research universities. The results show that environmental awareness positively relates with both perceived benefits and risks of nanotechnology, while the different effects of trust are contingent upon the actor in which trust is put. The contribution of the study point to the role of public trust in shaping perceptions of novel technology: the study's implications for practice thus inform the development of information strategies aimed at supporting the acceptance of KETs among the larger public.